SANITATION OVERVIEW OF SALT PROCESSING IN OEBELO VILLAGE, KUPANG REGENCY - Klau, Maria Septyani; Sahdan, Mustakim; Geghi, Cathrin W. G.; Setyobudi, Agus (HEARTY, 2026)
Sanitation plays a crucial role in salt processing to ensure the quality and safety of salt for consumer consumption. Salt processing conducted under high sanitation standards has a positive impact on the quality of the salt produced. This study aims to investigate the sanitation condition of salt processing in Oebelo, Kupang Regency. The research design is descriptive observational with a survey approach. The sample size consists of 31 salt-processing household in Oebelo. The result of the study indicate that all 31 salt production facilities in Oebelo Village, Kupang Regency, meet the health standards for salt processing sanitation. The variables that fall under category of meeting health standards include location and enviroment; production equipment; water supply/facilities for water provision; employee health and hygiene; maintenance anda sanitation hygiene programs; and storage. The variables categorized as not meeting health standards are building and facilities; and hygiene and sanitation facilities and activities.